Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1051/0004-6361/201526992
|View full text |Cite
|
Sign up to set email alerts
|

Binary properties of CH and carbon-enhanced metal-poor stars

Abstract: The HERMES spectrograph installed on the 1.2-m Mercator telescope has been used to monitor the radial velocity of 13 lowmetallicity carbon stars, among which seven carbon-enhanced metal-poor (CEMP) stars and six CH stars (including HIP 53522, a new member of the family, as revealed by a detailed abundance study). All stars but one show clear evidence for binarity. New orbits are obtained for eight systems. The sample covers an extended range in orbital periods, extending from 3.4 d (for the dwarf carbon star H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 100 publications
(165 reference statements)
7
92
2
1
Order By: Relevance
“…-HE 0111−1346 and HE 0507−1653 were also observed extensively by Jorissen et al (2016b), with results agreeing with ours within the errors. -HE 0430−1609 and HE 1523−1155 have suspiciously low rms errors for their orbital solutions.…”
Section: Cemp-s Starssupporting
confidence: 91%
See 2 more Smart Citations
“…-HE 0111−1346 and HE 0507−1653 were also observed extensively by Jorissen et al (2016b), with results agreeing with ours within the errors. -HE 0430−1609 and HE 1523−1155 have suspiciously low rms errors for their orbital solutions.…”
Section: Cemp-s Starssupporting
confidence: 91%
“…Signatures of similar pulsations in another two CEMP stars are found in the sample of Jorissen et al (2016b), but not among carbon-normal VMP/EMP r-process-enhanced stars. This suggests that the high molecular opacities of C-rich stellar atmospheres may be their source, but photometric confirmation of their existence and probable long periods in field stars is difficult from the ground.…”
Section: The Apparently Single Starsmentioning
confidence: 52%
See 1 more Smart Citation
“…However, we broadened the width of the window centered on Hα, from ±15 km s −1 used by Kürster et al (2003) for Barnard's star to ±45.68 km s −1 (±1 Å) It is worth to note, however, that HD 59686 A shows some similarities to carbon-enhanced metal-poor (CEMP) stars (see Beers & Christlieb 2005;Masseron et al 2010;Placco et al 2014) in the sense that these are evolved giants, they reside in binary systems, and the secondary is very likely a white dwarf (provided that HD 59686 B is confirmed to be a white dwarf). Recently, Jorissen et al (2016a) has identified low-amplitude RV variations superimposed on the binary trend in 3 CEMP stars in a sample of 13. They show periods of about one year and RV semi-amplitudes of hundreds of m/s.…”
Section: Spectral Activity Indicatorsmentioning
confidence: 99%
“…It is worth noting that neither pre-mass-transfer systems nor post-mass-transfer systems populate the avoidance zone in the bottom right corner of the (e-log P) plane (Mathieu 1994). The two exceptions, with P ∼ 3000-4000 days and 0.00 < e < 0.05, are due to the low accuracies of the eccentricities; high accuracies are difficult to obtain for such long-period systems, as discussed by Jorissen et al (2016).…”
Section: Resultsmentioning
confidence: 98%